KANDUNGAN Rhodamin Spada KERUPUK ESEK MERAH DIINDUSTRI RUMAH TANGGA DESA TLASIH KECAMATAN TULANGAN KABUPATEN SIDOARJO - Dessy Sylviana; Narwati .; Umi Rahayu (Poltekkes Kemenkes Surabaya, 2013)
Rhodamin B is a non-food synthetic dye which is misused on foods since it canendanger public health. The using of Rhodamin B is regulated by virtue of Republic ofIndonesia Minister of Health Regulation No. 239/MenKes/Per/V/85. The objective of this studyis to find out the content of Rhodamin Bqualitatively in red 'esek' chip.This study is a descriptive study that is to describe the existence of Rhodamin 8content in red 'esek' chip. The population of this study includes 250 grams red 'esek' chip from6 producers who produce red 'esek' chip at home industry of Desa Tlasih Kecamatan TulanganKabupaten Sidoarjo. Data analysis is performed descriptively namely by means of organolepticphysical examination, chemical examination and the knowledge level of red 'esek' chipproducers.The result of red 'esek' chip physical examination indicates that 2 out of 6 samples ofred 'esek' chip do not show any characteristic of Rhodamin 8 usage, while 4 samples of red'esek' chip show the characteristic of Rhodamin 8 usage. The evaluation of red 'esek' shipproducers' knowledge level indicates that 1 producer is categorized in